THE IMPACT OF ECONOMIC CONSIDERATIONS ON CONTRACTING WITH COMPANIES UNDER THE ENGLISH LAW - Rahmawati, Nooraini Dyah (Fortiori Law Journal, 2021)
Companies as the major contractual in the world as well as the biggest economical instrument, in which interconnected with one another by law and economy play an important role through their business activities in categorizing the core meaning and implementation of a contract and the evolution of its rules throughout centuries. This article offers a structural analysis and descriptive explanation on contract and consideration as well as the impact of economic consideration has on companies contractual relations by analysing some experts point of views, relevant cases, as well as practices under the English law through normative juridical with descriptive-analytical research specifications method. The gravity of the importance for companies in knowing how economical aspect is deemed crucial in formulating a business contract and how important its course for contract law in general, as it shows throughout time not only as part of companies preventive measure to avoid risks, but also an evolving mechanism within private law in general.